Public displays of affection : the album [compact disc] - Renea, Priscilla (Def Jam Recordings, 2022)
A soundtrack of intimacy that seemed to offer an answer: You let love lead. "I am a lover," Muni Long explains. "I prefer to be kind. I believe in fairytales. The reason Public Displays of Affection worked is because love was absent in R&B." For that breakthrough project, Muni wanted to mimic the ebbs and flows of a relationship, dipping and diving between moods and sounds - which is real, because love can be tumultuous, too.